Immunological effects of yogurt addition to a re-nutrition diet in a malnutrition experimental model - Gauffin Cano, María Paola (2002)
The therapeutic and preventive effects of yogurt and lactic acid bacteria on diseases such as cancer, infection and gastrointestinal disorders are well documented. The aim of this research was to study the effects of different doses of yogurt addition after milk re-nutrition diet, on the recovery of the intestinal barrier and mucosal immune function. Experiments were performed on groups of mice, malnourished and re-nourished with milk during 7 d, and mice with diet supplemented with yogurt for 2, 5 and 7 consecutive d. Nutritional parameters such as weight gain, serum total protein, and the number of IgA, IgM and IgG B cells of the small intestine were determined. We also quantified intraepithelial leukocytes, mastocytes and goblet cells, and performed structural and ultrastructural studies on the small intestine. We observed that 5 d of yogurt feeding was the optimal dose for improving gut barrier function and mucosal immune system in a malnutrition model. This effect was not observed with milk re-nutrition. Although the results were better for 5 d of yogurt, addition for 7 d also showed beneficial effects. Yogurt feeding in our model did not impair any gut functions. These results suggest that yogurt addition after a re-nutrition diet gives better recovery of intestinal function than the re-nutrition diet usually recommended. Although these results were obtained in an animal model, they indicate that consumption of yogurt by malnourished children might accelerate the restoration of gut function.